2018
DOI: 10.2174/1567205014666171121114930
|View full text |Cite
|
Sign up to set email alerts
|

A Speech Recognition-based Solution for the Automatic Detection of Mild Cognitive Impairment from Spontaneous Speech

Abstract: Background: Even today the reliable diagnosis of the prodromal stages of Alzheimer’s disease (AD) remains a great challenge. Our research focuses on the earliest detectable indicators of cognitive de-cline in mild cognitive impairment (MCI). Since the presence of language impairment has been reported even in the mild stage of AD, the aim of this study is to develop a sensitive neuropsychological screening method which is based on the analysis of spontaneous speech production during performing a memory task. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
187
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(225 citation statements)
references
References 39 publications
11
187
0
5
Order By: Relevance
“…Furthermore, we found that combining machine and multi-view learning can improve accuracy. The accuracies found here are comparable to the values reported by other authors, ranging from 60% to 85% (Prud'hommeaux and Roark, 2011;Lehr et al, 2012;Tóth et al, 2015;Vincze et al, 2016), which means that it is not easy to distinguish between healthy subjects and those with cognitive impairments. The comparison with our results is not straightforward, though, because the databases used in the studies are different.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, we found that combining machine and multi-view learning can improve accuracy. The accuracies found here are comparable to the values reported by other authors, ranging from 60% to 85% (Prud'hommeaux and Roark, 2011;Lehr et al, 2012;Tóth et al, 2015;Vincze et al, 2016), which means that it is not easy to distinguish between healthy subjects and those with cognitive impairments. The comparison with our results is not straightforward, though, because the databases used in the studies are different.…”
Section: Discussionsupporting
confidence: 86%
“…Ideally, it should be possible to administer them remotely, and they should integrate easily with existing telehealth and telecare solutions for older patients. Automated analysis of speech, in particular speech that is produced during a standard clinical assessment, might be a prime candidate for such a tool [9-14]. Several research groups demonstrated the interest of adopting an automated approach to speech analysis for clinical assessment of older people [15-19].…”
Section: Introductionmentioning
confidence: 99%
“…We used our custom DNN implementation for GPU, which achieved out- standing results on several datasets (e.g. [24,25,26,27,28]). We used 40 mel filter bank energies as features along with their first and second order derivatives.…”
Section: Methodsmentioning
confidence: 99%